Latency of Fluid Antenna Systems in Mobile Devices: Is a Liquid-Metal Slug Too Sluggish? - Evans, Adrian (Wellington Faculty of Engineering Symposium, 2023)
Mobile communication devices like smartphones, tablets and smartwatches benefit from having multiple internal antennas as far apart as possible to reduce the spatial correlation between receiving antennas and increase channel capacity. However, the small form factor of such devices means that a substantial separation distance is not practical. Additionally, it is not always possible to reduce the size of the antennas to increase the separation distance. Fluid antenna systems are a recently proposed technology in which the physical position of a reconfigurable antenna can be changed to pick up the strongest signal. This project considered a fluid antenna system for a mobile device in which a slug of liquid metal can move to different positions or ‘ports’ in an electrolyte-filled tube upon exposure to a voltage pulse. In light of the spatial variation in signal strength along the tube, algorithms are designed to control the channel selection and movement of the slug. The project compared the performance of a single-tube system with a fixed-location antenna. Simulation results and analysis demonstrate that the conventional fixed-location antenna outperforms the single-tube system due to the latency in transmission caused by the slug’s movement. As a result, two modifications were explored to reduce latency. First, the fixed antenna is made available as a backup to address the outage during slug movement. Secondly, a novel two-tube fluid antenna system was designed to separate the transmission and channel selection functions into different tubes.